Long coronary artery aneurysm treated by two graft stents on a single bare metal stent scaffold - Karapinar, Hekim; Kucukdurmaz, Zekeriya; Gümrükçüoğlu, Hasan Ali; Yilmaz, Ahmet (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2012)
We report a case of a 61-year-old male who presented with symptoms of stable angina. The coronary angiography revealed a long aneurysm and significant stenosis after the aneurysmatic segment on the circumflex artery. The length of the aneurysm was 21 mm with the largest diameter 9 mm. We thought that single graft stent placement was not possible due to the angled circumflex artery, length of the aneurysm and inflexible nature of graft stents. Distal stenosis was stented as usual. A bare metal stent was implanted over the aneurysm from normal to normal segments. Two graft stents were implanted sequentially in the aneurysm over the bare metal stent scaffold. Stent grafts covered the aneurysm without any main side branch occlusion. The patient was discharged the next day without any complications. The patient was asymptomatic after two years of follow-up with usual medications.